Innovative Strategies to Enhance the Quality of Higher Education Management: Human Resource Development and the Critical Role of Communication - Tusriyanto; Siminto; Az Zaakiyyah, Hizbul Khootimah (PT. LITERASI SAINS NUSANTARA, 2024)
Higher education plays a pivotal role in developing high-quality and competitive human resources. In this era of globalization, the dynamics of higher education environments are becoming increasingly complex, requiring innovative management to address challenges and ensure quality improvement. This research aims to elucidate innovative strategies for enhancing the quality of higher education management through human resource development and the critical role of communication. The study employs a qualitative literature review method with a literature search approach on academic sources. The primary data sources are obtained from Google Scholar, an online scholarly search platform, encompassing articles, books, theses, and other academic publications. The data collection period spans from 2013 to 2024, ensuring that the literature used is relatively recent and relevant to the current research context. The study's findings indicate that in the face of the increasingly complex dynamics of higher education, the successful implementation of innovative strategies to enhance the quality of higher education management is crucial. From the aforementioned exposition, it can be concluded that human resource development, collaboration with industries, the critical role of communication, and the utilization of technology are the main pillars that can guide higher education institutions towards greater achievements.